SYNTHESIS AND STRUCTURE OF DIETHYL-2,6-DIMETHYL-PYRIDIN-3,5-DICARBOXYLATE - O.A. Nurkenov; Seilkhanov T.M.; Fazylov S.D; Karipova G.Zh; Ermek D.M.; Tishtykbayeva D.E (Academic Scientific Journal of Chemistry, 2020)
The article is devoted to the development of a preparatively convenient method for the synthesis of diethyl-2,6-dimethylpyridin-3,5-dicarboxylate. The data on the synthesis of diethyl-2,6-dimethyl-1,4- dihydropyridine-3,5-dicarboxylate obtained by three-component cyclocondensation of two equimolar amounts of acetoacetic ester, urotropine and ammonium acetate by the Ganch method are presented. It was shown that when ethanol was boiled for 2 h, diethyl 2,6-dimethyl-1,4-dihydropyridin-3,5-dicarboxylate with sodium nitrite in acetic acid led to the formation of the corresponding aromatic pyridine. The structures of the synthesized compounds were studied by 1 H and 13C NMR spectroscopy, as well as by the data of two-dimensional spectra of COSY (1 H-1 H) and HMQC (1 H-13C). The values of chemical shifts, multiplicity, and integrated intensity of 1H and 13C signals in onedimensional NMR spectra were determined. Using spectra in the formats COSY (1 Н1 Н) and HMQC (1 Н13С), homo- and heteronuclear interactions were established, confirming the structure of the studied compounds